Oxytocin receptor gene variation, behavioural inhibition, and adult separation anxiety: Role in complicated grief. (18th August 2018) - Schiele, Miriam A.; Costa, Barbara; Abelli, Marianna; Martini, Claudia; Baldwin, David S.; Domschke, Katharina; Pini, Stefano
Abstract: Objectives: Complicated grief (CG) following bereavement significantly increases the risk for mood and anxiety disorders. The severity of grief reactions may be interactively influenced by temperamental and psychological factors such as behavioural inhibition (BI) and separation anxiety (SA) as well as biological factors. Given its central role in attachment and stress processing, a genetic variant in the oxytocin receptor ( OXTR ) gene was thus investigated in order to elucidate the direction of association as well as its interaction with BI and SA in the moderation of CG severity. Methods: Ninety-three patients with mood and anxiety disorders were evaluated for CG by means of the Inventory of Complicated Grief (ICG), for BI using the Retrospective Self-Report of Inhibition (RSRI), and for symptoms of SA during adulthood using the Adult Separation Anxiety Scale (ASA-27). All patients were genotyped for OXTR rs2254298. Results: OXTR genotype interacted with BI and, on a trend-level, with adult SA, to increase CG. Specifically, higher levels on the RSRI and ASA-27 scales, respectively, were related to higher ICG scores in GG genotype carriers. Conclusions: The present study for the first time suggests a gene–environment interaction effect of an OXTR gene variant with BI and possibly also symptoms of adult SA in the moderation of vulnerability for CG.